Interspecies Variation of In Vitro Stability and Metabolic Diversity of YZG-331, a Promising Sedative-Hypnotic Compound - Liu, Zhihao; Yang, Yakun; Sheng, Li; Li, Yan (Frontiers in Pharmacology, 2017)
YZG-331, a synthetic adenosine derivative, express the sedative and hypnotic effects via binding to the adenosine receptor. The current study was taken to investigate the metabolic pathway of YZG-331 as well as species-specific differences in vitro. YZG-331 was reduced by 14%, 11%, 6%, 46% and 11% within 120 min incubation in human, monkey, dog, rat and mouse liver microsomes (LMs), respectively. However, YZG-331 was stable in human, monkey, dog, rat and mouse liver cytoplasm with or without NADPH. In addition, YZG-331 was unstable in rat or mouse gut microbiota with more than 50 % of prototype drug degraded within 120 min incubation. Interestingly, the systemic exposure of M2 and M3 in rats and mice treated with antibiotics were significantly decreased in the pseudo germ-free (PGF) group. YZG-331 could be metabolized in rat and human liver under the catalysis of CYP enzymes, and the metabolism showed species variation. In addition, 3 phase I metabolites were identified via hydroxyl (M1), hydrolysis (M2), or hydrolysis/ hydroxyl (M3) pathway. Flavin-containing monooxygenase 1 (FMO1) and FMO3 participated in the conversion of YZG-331 in rat LMs. Nevertheless, YZG-331 expressed stability with recombinant human FMOs, which further confirmed the species variation in the metabolism. Overall, these studies suggested that YZG-331 is not stable in LMs and gut microbiota. CYP450 enzymes and FMOs mediated the metabolism of YZG-331, and the metabolic pathway showed species difference. Special attention must be paid when extrapolating data from other species to humans.